UPAYA INDONESIA DALAM MENINGKATKAN EKSPOR BATUBARA KE TIONGKOK PADA TAHUN 2019-2021 - Putri, Trisna Madani; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This article aims to research and understand Indonesia's efforts to increase coal exports which experienced a decline during the Covid-19 pandemic to China in 2019-2021. The main focus of this article is Indonesia's role in increasing seaweed exports to China during the pandemic. This article uses a liberalism perspective with a nation state level of analysis. This paper also uses the international trade theory of Heckscher-Ohlin. The method used in this paper is qualitative research and is explanatory in nature by searching several literatures such as books, journals, internet articles, as well as various sources combined and used to complete the needs of this paper.The result of this article is that Indonesia is taking strategic steps as a form of effort to increase coal exports to China during the Covid-19 pandemic. The result of this article is that Indonesia is taking strategic steps as a form of effort to increase coal exports to China during the Covid-19 pandemic. The efforts made are to increase international cooperation between Indonesia and China by utilizing this cooperation, namely the China-Indonesia Coal Procurement Matchmaking Meeting, creating a program to improve coal quality, namely the road map program for the development and utilization of coal for 2021-2045, controlling global coal prices. by emphasizing domestic production volumes and the Indonesian finance minister created a policy stimulus in the form of facilitating export services in the midst of the pandemic. With these efforts, the value of Indonesian coal exports to China managed to increase to 9,143.1 US and the export volume also increased to 108,487.2 tons. Keywords: Coal Exports, Indonesian Coal, China, Covid-19